Three new species of 'tetraphyllidean' cestodes from an undescribed bamboo shark (Orectolobiformes: Hemiscylliidae) in Sri Lanka - Caira, Janine N; Otto, Kyle; Fernando, Daniel; Jensen, Kirsten (Folia parasitologica, 2021)
Examination of seven specimens of an undescribed species of bamboo shark (Orectolobiformes: Hemiscylliidae), currently referred to as Chiloscyllium sp. 1, from Sri Lanka yielded three new species of 'tetraphyllidean' cestodes, one each in the genera Carpobothrium Shipley et Hornell, 1906, Spiniloculus Southwell, 1925, and Yorkeria Southwell, 1927. Carpobothrium marjorieae Caira, Otto et Jensen sp. n. differs from its three valid congeners in total length, number of testes, and size of the apical sucker of its anterior bothridial flap. Like Carpobothrium eleanorae Koontz et Caira, 2016 it possesses spherical eggs with highly elongate bipolar filaments, but its eggs are conspicuously larger than those of the latter species. Spiniloculus akshayi Caira, Otto et Jensen sp. n. can be distinguished from its five congeners in total length and number of proglottids. Yorkeria sachiniae Caira, Otto et Jensen sp. n. differs from its 16 congeners in number of proglottids and testes, total length, terminal proglottid, cirrus sac, and cephalic peduncle length, hook size, genital pore position, and bothridial shape. The eggs of Y. sachiniae Caira, Otto et Jensen sp. n. are spindle-shaped and bear a single long, polar filament. All three species were found to exhibit microthrix patterns on their scolices like those of the majority of their congeners that have been examined to date with scanning electron microscopy. Microtriches on the distal surfaces of the bothridial pouches of a species of Carpobothrium were characterised for the first time; C. marjorieae Caira, Otto et Jensen sp. n. was found to possess a modified form of gladiate spinithrix on this surface. Among the seven members of the genus, this is the first species of Chiloscyllium Müller et Henle that has been found to host representatives of all three of these 'tetraphyllidean' genera. However, unlike most of its congeners, a representative of the non-hooked genus Scyphophyllidium Woodland, 1927 was not found infecting Chiloscyllium sp. 1.
Keywords: Animals; Sri Lanka; Female; Classification; Cestoda; Microscopy, Electron, Scanning; žraloci; ženské pohlaví; Testis; cestodózy; nemoci ryb; mikroskopie elektronová rastrovací; Fish Diseases; klasifikace; testis; Sharks; Male; Srí Lanka; Cestode Infections; zvířata; mužské pohlaví